Effect of additive cellulase on fermentation quality of whole-plant corn silage ensiling by a Bacillus inoculant and dynamic microbial community analysis - Liu, Xudong; Wang, Aifang; Zhu, Liqi; Guo, Wei; Guo, Xiaojun; Zhu, Baocheng; Yang, Ming (Frontiers in Microbiology, 2024)
Whole-plant corn silage (WPCS) has been widely used as the main roughage for ruminant, which promoted the utilization of corn stover for animal feed production. However, rigid cell wall structure of corn stover limits the fiber digestion and nutrients adsorption of WPCS. This study investigated the effect of adding cellulase on improving the fermentation quality of WPCS ensiling with a Bacillus complex inoculant. With the Bacillus (BA), the lactic acid accumulation in the WPCS was significantly higher than that in control (CK). The additive cellulase (BC) increased the lactic acid content to the highest of 8.2% DW at 60 days, which was significantly higher than that in the CK and BA groups, and it reduced the neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents from 42.5 to 31.7% DW and 28.4 to 20.3% DW, respectively, which were significantly lower than that in the CK and BA groups. The crude protein and starch were not obviously lost. Dynamic microbial community analysis showed that the Bacillus inoculant promoted the lactic acid bacteria (LAB) fermentation, because higher abundance of Lactobacillus as the dominant bacteria was observed in BA group. Although the addition of cellulase slowed the Lactobacillus fermentation, it increased the bacterial community, where potential lignocellulolytic microorganisms and more functional enzymes were observed, thus leading to the significant degradation of NDF and ADF. The results revealed the mechanism behind the degradation of NDF and ADF in corn stover, and also suggested the potential of cellulase for improving the nutritional quality of WPCS.